HOW LITERATE AM I ABOUT ASSESSMENT: EVIDENCE FROM INDONESIAN EFL PRE-SERVICE AND IN-SERVICE TEACHERS - Nanin Verina Widya Putri; Syafi’ul Anam (English Review: Journal of English Education, 2021)
Language Assessment Literacy (LAL) for teachers is a pivotal content area which teachers must have for their prefessional development. Despite increasing interest in language assessment, research focusing on LAL of pre-service and in-service teachers, especially in Indonesian EFL context, has yet to receive due attention. Nevertheless, understanding pre-service and in-service teachers’ literacy of classroom assessment is essential for the quality of classroom assessment practice, hence the improvement of language learning and teaching. This study aimed to investigate Indonesian EFL pre-service and in-service teachers’ literacy of classroom assessment. Using a quantitative approach with ex-post facto research design, this study examined the extent of assessment literacy among EFL pre-service and in-service teachers. Participants were 60 English department students who have done teaching practicum courses and 41 in-service teachers in the Indonesian province of East Java. The finding revealed that the pre-service and in-service teachers perceived a moderate level of assessment literacy. Further, the two groups of participants demonstrated a statistically significant difference in overall assessment literacy, as well as in two of its dimensions, namely administering and scoring assessment results and alternative assessment. The findings of this study could shed light to the understanding of EFL pre-service and in-service teachers’ literacy of classroom assessment.